Synthesis and evaluation of new radioligands [(11)C]A-833834 and [(11)C]A-752274 for positron-emission tomography of α7-nicotinic acetylcholine receptors - Horti, Andrew G. (2013)
INTRODUCTION: α7-nicotinic acetylcholine receptor (α7-nAChR) is one of the major neuronal nAChR subtypes. α7-nAChR is involved in variety of neuronal processes and disorders including schizophrenia and Alzheimer’s disease. A number of α7-nAChR PET radioligands have been developed, but a quality radiotracer remains to be discovered. METHODS: High binding affinity α7-nAChR ligands A-833834 and A-752274 were radiolabeled with (11)C. Baseline and blockade biodistribution studies in the mouse brain of [(11)C]A-833834 (5-(6-(5-[(11)C]methylhexahydropyrrolo[3,4-c]pyrrol-2(1H)-yl)pyridazin-3-yl)-1H-indole) and [(11)C]A-752274 (2-(6-[(11)C]methyl-3,6-diazabicyclo[3.2.0]heptan-3-yl)-7-(6-methyl-3,6-diazabicyclo[3.2.0]heptan-3-yl)-9H-fluoren-9-one) were performed. [(11)C]A-752274 was evaluated in a baseline baboon PET study. RESULTS: [(11)C]A-833834 and [(11)C]A-752274 were synthesized by radiomethylation of corresponding des-methyl precursors. The radioligands were prepared with radiochemical yield of 12–32%, high specific radioactivity (330–403 GBq/μmol) and radiochemical purity > 95%. Dissection studies with [(11)C]A-833834 demonstrated low specific α7-nAChR binding in the mouse brain. [(11)C]A-752274 specifically (~50%) labeled α7-nAChR in the mouse thalamus. However, [(11)C]A-752274 exhibited low brain uptake in baboon (%SUV<100). CONCLUSION: Two novel α7-nAChR ligands radioligands were synthesized and studied in animals. Specific binding of [(11)C]A-833834 in the mouse brain is low due to the insufficient binding affinity of the radioligand. The very high binding affinity [(11)C]A-752274 exhibited good specific binding in the α7-nAChR – rich mouse brain regions. The low uptake of [(11)C]A-752274 in the baboon brain is due to its high hydrophilicity, rapid metabolism or other properties. Future development of α7-nAChR PET radioligands will be based on compounds with high binding affinities and good blood-brain barrier permeability.